Detection of some Food Poisoning Bacteria from Milk Utensils and Dairy Products in Port-said Governorate, Egypt - Saad, Ahmed H.; El-kosi, Omar H. Refaat; Salma, Ehab M.; El hadidi, Mira M. (Journal of Advanced Veterinary Research, 2023)
The aim of this study is to determine the possibility of transmission of some food poisoning bacteria (Staphylococcus aureus, Streptococcus spp., Escherichia coli and Proteus spp.) from the surfaces of equipment and utensils used in small dairy shops for production of dairy products to the final dairy products through microbiological examination of 90 swabs which were collected from the surfaces of equipment and utensils in small dairy shops from different localities at Port-said governorate, Egypt, in addition to 45 of each commercial small scale yoghurt and rice with milk pudding samples collected from the same small dairy shops. The results showed that the mean values for Staphylococcus aureus counts were 4.7Ã—10âµÂ±1.0Ã—10âµ cfu/g, 3.9Ã—10âµÂ±8.8Ã—10â´ cfu/g and 9.4Ã—10âµÂ±2.3Ã—10âµ cfu/g in swabs, yoghurt and rice with milk pudding samples, respectively, and The mean values for Streptococcus spp. were 2.2Ã—10â¶Â±2.6Ã—10âµ cfu/g,1.4Ã—10â¶Â±3.1Ã—10âµcfu/g and 3.2Ã—10â¶Â±5.6Ã—10âµ cfu/g in swabs, yoghurt and rice with milk pudding samples, respectively, While the mean values of Escherichia coli were 1.7Ã—10Â²Â±2.6Ã—10Â¹ cfu/g and 1.2Ã—10Â²Â±3Ã—10Â¹ cfu/g in swabs and yoghurt samples, respectively, with absence in examined rice with milk pudding samples. Proteus spp. couldnâ€™t be detected in any examined samples. It could be concluded that the microorganisms which isolated from yoghurt and rice with milk pudding samples have already found on equipment and utensils used in its manufacture, this may confirm cross-contamination from equipment and utensils surfaces to yoghurt and rice with milk pudding as a final dairy product of small dairy shops.